Designing the Methodology for the Development of Students’ Emotional Intelligence in Terms of Digital Transformation - Osova , Olha (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The problem of the development of students’ emotional intelligence has always been crucial for their future professional activity, and is acquiring particular significance during present stage of humans’ development and educational transformation. In this context a foreign language is not only an important means of communication but also an effective tool for self-development and formation of emotional intelligence, that in its turn requires reconsideration of existing educational strategies and methods.The aim of this article is to ground theoretical knowledge and design methodology for the development of students’ emotional intelligence by means of a foreign language in terms of digital transformation. The object of the article is the process of the development of students’ emotional intelligence, and the subject is the design of the methodology of the development of students’ emotional intelligence by means of a foreign language in terms of digital transformation. In the article analyzed are the essence and components of emotional intelligence in the terms of education. Emotional intelligence of students in higher education is viewed as an integrated feature of the individual that synthesizes cognitive, emotional and behavioral components and presupposes effective adaptation to the dynamic nature of education and future professional activities. The article defines the specific impact of digital environment on development of emotional intelligence during foreign language education. The designed methodology of the development of emotional intelligence is grounded on systemic approach that comprises the embodiment of authentic materials, reflexive practices, interactive tasks as well as digital tools. The methodology integrates fundamental and specific principles of training aimed at the use of digital technologies that entails the development of emotional competence while foreign language education. Special attention is paid at the use of AI in simulating emotionally infiltrated dialogues and also feedback. The article presents example exercises and tasks that are pertinent to the framework of designed methodology and are aimed at activation of students’ emotional and communicative experience.